The EIB in the city Investment on the agenda (Volume 9) - Clark, Greg (European Investment Bank, 2019)
"City, transformed" has shown how Europe's cities have developed over the last 50 years. The European Investment Bank has adapted alongside them, building a greater, more focused role in urban development that takes it into truly innovative areas. Future cities need to face up to challenges in climate, productivity, knowledge, social mobility and resilience. Here's how the EU bank is setting up to be a partner on that path.